Pemanfaatan Media Pembelajaran Berbasis Gamifikasi dalam Proses Pembelajaran di MIS Terpadu Al-Azhfar - Hakeu, Febrianto; Pakaya, Idan I.; Tangkudung, Mutmain (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to investigate the impact of gamification-based learning media in the learning process at MIS Terpadu Al-Azhfar North Gorontalo, focusing on student motivation and learning outcomes. This type of research is descriptive qualitative to gain an in-depth understanding of the use of gamification-based learning media by teachers at MIS Terpadu Al-Azhfar North Gorontalo. Based on the results of the study, it can be seen that the teachers of MIS Terpadu Al-Azhfar North Gorontalo have yet to maximize the use of gamification-based learning media, so learning is less fun and ineffective, students seem inactive in the learning process There is no two-way communication between teachers and students. In addition, there is no teacher creativity in making the class more fun, and teacher mastery of the class could be better, resulting in a lack of student interest to focus on learning in the classroom. A trial of the use of Gamification-based learning media in the learning process at the Integrated MIS Terpadu Al-Azhfar shows that the use of gamification-based learning media positively impacts learning motivation and student engagement. Teachers who integrate game elements in learning successfully create an engaging and dynamic learning environment. Students show greater interest in education and are more eager to participate in learning activities. Student academic outcomes also improved, with an improved understanding of concepts and critical thinking skills.